Noninvasive brain stimulation for the treatment of auditory verbal hallucinations in schizophrenia: methods, effects and challenges - Kubera, Katharina Maria; Barth, Anja; Hirjak, Dusan; Thomann, Philipp; Wolf, Robert Christian (Frontiers in systems neuroscience, 2015)
This mini-review focuses on noninvasive brain stimulation techniques as an augmentation method for the treatment of persistent auditory verbal hallucinations (AVH) in patients with schizophrenia. Paradigmatically, we place emphasis on transcranial magnetic stimulation (TMS). We specifically discuss rationales of stimulation and consider methodological questions together with issues of phenotypic diversity in individuals with drug-refractory and persistent AVH. Eventually, we provide a brief outlook for future investigations and treatment directions. Taken together, current evidence suggests TMS as a promising method in the treatment of AVH. Low-frequency stimulation of the superior temporal cortex may reduce symptom severity and frequency. Yet clinical effects are of relatively short duration and effect sizes appear to decrease over time along with publication of larger trials. Apart from considering other innovative stimulation techniques, such as transcranial Direct Current Stimulation, and optimizing stimulation protocols, treatment of AVH using noninvasive brain stimulation will essentially rely on accurate identification of potential responders and non-responders for these treatment modalities. In this regard, future studies will need to consider distinct phenotypic presentations of AVH in patients with schizophrenia, together with the putative functional neurocircuitry underlying these phenotypes.
Gesehen am 02.06.2020